Festival Beeldende Muziek 1986. (Hasselt : Provinciaal Museum, 1986)
Fox, Terry ; Julius ; Mertens, Wim ; Eastly, Max ; Fox, Terry ; Vivenza ; Vogel, Peter
Festival Beeldende Muziek 1986, Provinciaal Museum, Hasselt, 26 april - 1 juni 1986
boek